Characterization of Chemically Treated Sisal Fiber/Polyester Composites - Adane Adugna Ayalew; Awoke Fenta Wodag (Journal of Engineering)
Natural fibers have the potential to replace synthetic fibers for making polymer composites due to their remarkable properties. Polyester is one of the core materiel used for textile and leather due to hydrophobic property. Sisal fibers have high strength among various naturals and can be used as the supporting material for polymers. A detailed experimental study was conducted for the extraction of sisal fiber and composite development. The fibers were treated by using 2%, 6%, and 10% NaOH concentrations within 24, 48, and 72 h soaking time. Composite was made from different sisal to polyester ratios of 20 : 80, 30 : 70, and 40 : 60 (w/w). Mechanical properties such as tensile strength and flexural strength of treated, untreated, and reinforced fibers were determined. Functional groups of both the treated and untreated sisal fibers were characterized using Fourier transform infrared spectroscopy (FTIR). The thermal stability of sisal fiber was analyzed by thermogravimetric analysis (TGA). The optimum tensile strength and bending strength of the composite were found at 44.0 MPa and 50.8 MPa for fiber with polyester ratio of 30 : 70, 6% NaOH concentration, and 48 h soaking time. It is confirmed that treated sisal fiber-reinforced polyester composites have better tensile and bending properties and lower water absorption than untreated fibers.